Involvement of transforming growth factor beta 1 in the transcriptional regulation of nicotinamide N-methyltransferase in clear cell renal cell carcinoma - Campagna, Roberto; Cecati, Monia; Pozzi, Valentina; Fumarola, Stefania; Pompei, Veronica; Milanese, Giulio; Galosi, Andrea Benedetto; Sartini, Davide; Emanuelli, Monica (Cellular and Molecular Biology, 2018)
Renal cell carcinoma (RCC) is the most common tumor of the kidney and its major histologic subtype is clear cell RCC (ccRCC). About 30% of diagnosed ccRCCs already have metastasis. Traditionally, localized ccRCC is treated with nephrectomy but the relapse rate is 30%. Thus, the discovery of effective biomarkers for early detection, as well as the identification of new targets for molecular-based therapy of ccRCC are urgently required. In this study, we focused on molecules that could modulate the trascription of the enzyme nicotinamide N-methyltransferase (NNMT) that is known to be up-regulated in ccRCC. Signal transducer and activator of transcription 3 (STAT3), interleukin 6 (IL-6), hepatocyte nuclear factor 1 beta (HNF-1Î²) and transforming growth factor beta 1 (TGF-Î²1) expression levels were determined in tumor and non tumor samples obtained from 30 patients with ccRCC, using Real-Time PCR. Results obtained showed that TGF-Î²1 is significantly (p<0.05) overexpressed in tumor compared with normal tissue samples of ccRCC patients. Conversely, we did not find any statistically significant difference concerning STAT3, IL-6, HNF-1Î² gene expression levels. TGF-Î²1 up-regulation could be responsible for the high levels of NNMT observed in ccRCC. Targeting TGF-Î²1 could improve the outcome of ccRCC patients due to its role in epithelial-mesenchymal transition (EMT), that is known to be associated with a worse overall survival (OS) in this neoplasm.